Determination of extractive content in Cupressus sempervirens wood through a NIRS-PLSR model and its correlation with durability. (August 2021) - Palanti, Sabrina; Alves, Ana; Rodrigues, José; Danti, Roberto
Abstract: The objective of this study was the development of a NIRS (Near InfraRed Spectroscopy) and PLSR (Partial Least Square Regression) model for quantitatively determining extractives, in four clones of the Italian cypress Cupressus sempervirens . Extractives were correlated to the fungal resistance of wood samples evaluated with a non-standard procedure based on the mass loss of mini-blocks. PLSR regression models based on NIRS gave good predictions of extractives content with RPD (Residual Prediction Deviation) equal or above 2.7, suggesting that NIRS-PLSR procedure could be used for the characterization of cypress wood. Total extractives were significantly different among heartwood and sapwood but not among clones. Both inner and outer heartwood of the four C. sempervirens clones were resistant to three brown rot fungi. Minimal differences were found among clones in the mass loss of the heartwood samples, while significant inter-clonal differences emerged in the mass loss of sapwood samples. Intra-clonal variation was detected for sapwood samples and only in one of the four tested clones. The correlation between durability and extractives content was significant only if sapwood was added to heartwood in the dataset. Nevertheless, the high durability observed in the examined clones encourages selection of these cypress genotypes for wood production. Highlights: A NIR based PLSR was developed for determining extractives in clones of C. sempervirens. The biological resistance to fungal decay of C. sempervirens was determined for first time. The NIR Based PLSR model worked only if the sapwood resistance was considered.